Recognizing Possibilities of Computational Tinking When Teaching First-degree Equations - Barbosa, Luciana Leal da Silva (2019)
This work aims to present a hands-on activity for the first degree equations. The activity was applied to a reinforcement class of the K-8, in a public school in Birigui, Sao Paulo, Brazil. The activity used the Balance of Equations game, built on the Scratch programming environment with the objective of teaching the initial ideas of frst degree equations to a class with a learning gap in this discipline. The planning of the activity was divided into three moments, with the intention of starting from an analogy to the principle of equivalence of an equation, reaching the algebraic transcription of an equation through activities of manipulation of the game code. Seven concepts related to computational thinking with strong potential to be worked during the activity were identifed. In this way, besides the presentation of the classroom case, this article identifes these seven concepts, analyzing how they could be developed during the application of the activity, seeking to answer the following question: How can computational thinking skills be explored through hands-on activity for the teaching of equations?